2019
DOI: 10.1002/hpm.2881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mediterranean diet adherence in university student populations: Does this dietary pattern affect students' academic performance and mental health?

Abstract: Summary Adherence to a healthy diet such as Mediterranean Diet (MD) may exert beneficial effects in university students, promoting their academic performance and quality of life, as well as their mental and physical health status. In this aspect, the present study aimed to critically analyze the current epidemiological evidence concerning MD adherence of university students' populations. PubMed database was comprehensively searched, using relative keywords. Students' dietary habits are moving away from MD guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 56 publications
(77 reference statements)
3
51
2
4
Order By: Relevance
“…Students who adhere to a Mediterranean diet consider their health to be in better condition, have improved sleep and report low levels of stress [47]. These observations are supported by our results, as the participants in our study showed greater resistance to physical exercise than those who did not follow a Mediterranean diet, both in standard conditions and in more hostile environments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Students who adhere to a Mediterranean diet consider their health to be in better condition, have improved sleep and report low levels of stress [47]. These observations are supported by our results, as the participants in our study showed greater resistance to physical exercise than those who did not follow a Mediterranean diet, both in standard conditions and in more hostile environments.…”
Section: Discussionsupporting
confidence: 89%
“…Lifestyle and eating habits are directly associated with physical and mental health [47][48][49][50][51][52][53]. Due to the importance they have in the population, first responders are an important study population for assessing nutritional intervention and optimal physical activity in time and quality.…”
Section: Discussionmentioning
confidence: 99%
“…This factor of change makes it necessary to have a varied diet in foods such as the Mediterranean. It provides an improvement in living habits and provides the necessary nutrients [12,13]. The Mediterranean diet (MD) is rich in vegetables, fruits, legumes, nuts, and cereals, with olive oil as the basic dietary fat [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, adherence to a Mediterranean Diet (MD) was shown to be positively related with better academic success in college students. While a review of studies documented that poorer students health status was associated with lower MD adherence while inversely higher MD adherence was correlated with lower depression risk, whereas higher perceived stress score with lower fruit and vegetables intake [33]. Fruits and vegetables in particular, have been associated with a plethora of benefits attributed to their surplus of a rather wide variety of bioactive compounds [33,34].…”
Section: Discussionmentioning
confidence: 99%